2018
DOI: 10.3390/mi9020055
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of Micro-Array Channels with the Ultrafine-Grained LZ91 Mg-Li Alloy by Micro-Embossing

Abstract: The fabrication of the micro-channel array through micro-embossing on an ultrafine-grained (UFG) LZ91 Mg-Li alloy was investigated in this paper. Micro-embossing tests indicated that the depth of the channels increase with increasing temperatures. Micro-array channels with widths ranging from 50 μm to 200 μm were performed with an applied force of 2 kN at 423 K, following by a dwell time of 60 s on the UFG LZ91 Mg-Li alloy. The surface topography indicates that embossed micro-channels for UFG LZ91 Mg-Li with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Saotome et al investigated the effect of grain size on filling behavior during embossing process and found that the finer grain provided better filling ability. Similar phenomenon was also proved to be valid for the pure Al, pure Cu, pure Ni, and magnesium alloy . Thus, it was confirmed that grain size effect would influence the forming behavior during micro‐embossing and UFG‐grained materials were of better formability.…”
Section: Introductionsupporting
confidence: 69%
“…Saotome et al investigated the effect of grain size on filling behavior during embossing process and found that the finer grain provided better filling ability. Similar phenomenon was also proved to be valid for the pure Al, pure Cu, pure Ni, and magnesium alloy . Thus, it was confirmed that grain size effect would influence the forming behavior during micro‐embossing and UFG‐grained materials were of better formability.…”
Section: Introductionsupporting
confidence: 69%
“…4 shows the SEM-EDS image and XRD pattern of the Mg–8Li–2Y–Zn/Al multilayered composites. According to the binary phase diagram of the Mg–Li alloys and the literature, 21,22 the dual-phase alloy is mainly composed of a white α-Mg phase and a gray β-Li phase. From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 109 ] To address these problems, Xu et al [ 110 ] developed a novel microembossing tool with self‐ adjustment and a vacuum mounting system for fixing and protecting the fragile silicon die, as shown in Figure a. Microchannel arrays with dimensions of 5–100 µm, patterns of the HIT logo, name, and motto, were fabricated using the corresponding silicon die (as shown in Figure 8b–d) on the UFG pure Al [ 110,111 ] and LZ91 magnesium alloy, [ 112 ] as shown in Figure 8e–g. Then, quality evaluations were conducted by measuring the profile of the channel sidewall, the surface roughness, and the fully transferred patterns, and the results demonstrated significant potential in the mass production of MEMS components.…”
Section: Microforming Processes Of 3d Microstructuresmentioning
confidence: 99%